2006
DOI: 10.1128/jb.00896-06
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Inverted Repeat, the LipR Box, Mediates Transcriptional Activation of the Streptomyces exfoliatus Lipase Gene by LipR, a Member of the STAND Class of P-Loop Nucleoside Triphosphatases

Abstract: Expression of the Streptomyces exfoliatus lipA gene, which encodes an extracellular lipase, depends on LipR, a transcriptional activator that belongs to the STAND class of P-loop nucleoside triphosphatases. LipR is closely related to activators present in some antibiotic biosynthesis clusters of actinomycetes, forming the LipR/TchG family of regulators. In this work we showed that purified LipR protein is essential for activation of lipA transcription in vitro and that this transcription depends on the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…CrbR is a member of the LuxR family, whose members are known to recognize and bind inverted repeats (Evangelista-Martínez et al, 2006 ; Antunes et al, 2008 ). To identify any conserved motifs required for CrbR-mediated promoter induction, we obtained the sequence of the putative promoter region of acs homologs from 31 Gammaproteobacteria (Table 3 ) and ran a motif search using the MEME, a tool for the discovery of novel, ungapped motifs in sequences (Bailey et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…CrbR is a member of the LuxR family, whose members are known to recognize and bind inverted repeats (Evangelista-Martínez et al, 2006 ; Antunes et al, 2008 ). To identify any conserved motifs required for CrbR-mediated promoter induction, we obtained the sequence of the putative promoter region of acs homologs from 31 Gammaproteobacteria (Table 3 ) and ran a motif search using the MEME, a tool for the discovery of novel, ungapped motifs in sequences (Bailey et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…PcaR exerts its regulatory role by interacting with 15-bp operator sequences that are located in the pcaI-pcaR intergenic region and upstream of pcaH and pobA. PcaO is the first LAL-type regulator involved in aromatic compounds catabolism (Zhao et al 2010), although the involvement of LAL-type regulators in regulation of different metabolic pathways has been intensively characterized (Panagiotidis et al 1998;van Beilen et al 2001;Evangelista-Martínez et al 2006). In vitro EMSA results showed that ATP weakened the binding between PcaO and its target sequence but ADP strengthened this binding, while the effect of protocatechuate on PcaO binding was dependent on the protocatechuate concentration.…”
Section: Regulation Of Aromatic Compounds Metabolism In C Glutamicummentioning
confidence: 99%
“…The highest level of identity found was the level of identity between PcaO and a putative regulator of benzoate degradation (BenR, NCgl2324) of C. glutamicum (28% identity) (14,15,35). The levels of identity between PcaO and other LAL regulators, including LipR of Streptomyces coelicolor (42), LipR of Streptomyces exfoliatus (9), PikD of Streptomycoes venezuelae (47), AcoK of Klebsiella pneumoniae (27), AlkS of Pseudomonas oleovorans (48), and MalT of E. coli (29), were less than 20%. We concluded that this PcaO was a novel and atypical LAL-type regulator.…”
Section: Resultsmentioning
confidence: 99%
“…According to amino acid sequence analysis, PcaO is phylogenetically related to members of the previously proposed LAL subfamily of bac- PcaO is the first LAL-type regulator involved in catabolism of aromatic compounds, although the involvement of LALtype regulators in regulation of different metabolic activities has been intensively characterized. The MalT protein in E. coli regulates catabolism of maltose (24,29), the AlkS protein in P. oleovorans regulates degradation of medium-chain-length alkanes (43,48), the LipR proteins in S. exfoliatus and S. coelicolor regulate transcription of lipase (9,42), the AcoK protein in K. pneumoniae regulates acetoin degradation (27), and the PikD protein in S. venezuelae regulates pikromycin synthesis (47). It has been proposed that LAL-type regulators are involved in regulation of diverse types of metabolism in both Gram-negative and Gram-positive bacteria, but their regulatory mechanisms might be different.…”
Section: Discussionmentioning
confidence: 99%